A Mycobacterium tuberculosis Specific IgG3 Signature of Recurrent Tuberculosis - Fischinger, Stephanie; Cizmeci, Deniz; Shin, Sally; Davies, Leela; Grace, Patricia S.; Sivro, Aida; Yende-Zuma, Nonhlanhla; Streeck, Hendrik; Fortune, Sarah M.; Lauffenburger, Douglas A.; Naidoo, Kogieleum; Alter, Galit (Frontiers in Immunology, 2021)
South Africa has the highest prevalence of HIV and tuberculosis (TB) co-infection globally. Recurrent TB, caused by relapse or reinfection, makes up the majority of TB cases in South Africa, and HIV infected individuals have a greater likelihood of developing recurrent TB. Given that TB remains a leading cause of death for HIV infected individuals, and correlates of TB recurrence protection/risk have yet to be defined, here we sought to understand the antibody associated mechanisms of recurrent TB by investigating the humoral response in a longitudinal cohort of HIV co-infected individuals previously treated for TB with and without recurrent disease during follow-up, in order to identify antibody correlates of protection between individuals who do not have recurrent TB and individuals who do. We used a high-throughput, “systems serology” approach to profile biophysical and functional characteristics of antibodies targeting antigens from Mycobacterium tuberculosis (Mtb). Differences in antibody profiles were noted between individuals with and without recurrent TB, albeit these differences were largely observed close to the time of re-diagnosis. Individuals with recurrent TB had decreased Mtb-antigen specific IgG3 titers, but not other IgG subclasses or IgA, compared to control individuals. These data point to a potential role for Mtb-specific IgG3 responses as biomarkers or direct mediators of protective immunity against Mtb recurrence.